Preparation method of composite functional membrane and composite functional membrane
Patent Information
- Application Number
- CN202611137735.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]为了同时解决溶剂污染、溶剂残留、MOF团聚脱落、基材适配单一的问题,本申请提出了一种复合功能膜的制备方法及复合功能膜
本申请提供一种复合功能膜的制备方法,该方法包括:S1.提供基材和MOF粉体;所述基材包括改性纳米纤维素浆料、聚烯烃多孔隔膜中的任意一种;S2.将所述MOF粉体与水性粉体润滑剂,按预设质量比例干态均匀混合,得到复合粉体;S4.将所述复合粉体均匀喷淋于所述基材的表面,并利用机械辊压与微摩擦协同物理作用,驱动所述复合粉体均匀嵌入所述基材的表层及微孔内部,得到复合后的功能膜;针对所述改性纳米纤维素浆料,机械辊压与微摩擦协同物理作用后,MOF颗粒嵌入纤维交织网络,形成混凝土式三维网状复合结构;针对所述聚烯烃多孔隔膜,机械辊压与微摩擦协同物理作用后,MOF颗粒均匀锚固于隔膜表面与微孔通道;S5.对所述复合后的功能膜进行恒温固化,以强化所述MOF粉体与所述基材的界面结合强度,得到固化后的功能膜;S6.对所述固化后的功能膜进行后处理成型,得到复合功能膜。
Smart Images

Figure CN122889946A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the fields of nanocomposite functional materials and key membrane modification technology for new energy lithium batteries, specifically to a method for preparing a composite functional membrane and the composite functional membrane itself. Background Technology
[0002] Lithium-ion batteries are the core energy storage carriers for new energy power batteries, large-scale energy storage, and portable electronic devices. As the core isolation and ion transport functional component of the battery, the separator's wettability, ion transport uniformity, high-temperature dimensional stability, and interfacial bonding stability directly determine the battery's cycle life, rate performance, and safety threshold.
[0003] Metal-organic framework (MOF) materials are among the best functional fillers for the functional modification of lithium battery separators due to their ultra-high specific surface area, precise controllable pore size, and excellent lithium-ion selective permeability.
[0004] However, the MOF lithium-ion battery separator modification technologies in related fields all employ organic solvent liquid-phase process systems such as solvothermal, in-situ liquid-phase growth, wet coating, and solution impregnation, which have the following drawbacks: First, the processes are highly dependent on toxic organic solvents such as DMF (N,N-dimethylformamide), NMP (N-methylpyrrolidone), and methanol, resulting in high environmental disposal costs and failing to comply with the new energy green and low-carbon mass production policy; second, organic solvents are easily adsorbed and retained in the separator micropores and MOF channels, and conventional drying and annealing post-treatment cannot completely remove them, with residual solvents persisting during battery charge-discharge cycles. The decomposition process generates gas, leading to battery swelling, increased interfacial impedance, and a sharp decline in cycle life. Third, MOF nanoparticles in liquid solvent systems have extremely high surface energy, making them prone to aggregation and sedimentation with poor dispersion uniformity. Furthermore, MOFs adhere to the membrane surface solely through physical adsorption, resulting in extremely low interfacial bonding strength. They are prone to detachment and failure during long-term charge-discharge cycles, leading to poor modification durability and batch-to-batch consistency. Fourth, traditional wet processes have limited substrate compatibility, only adapting to single substrates such as nanofibers or polyolefins. They cannot achieve universal and stable modification of dual substrates, resulting in narrow industrial application scenarios and insufficient mass production versatility.
[0005] Therefore, it is particularly important to provide a method for preparing a composite functional membrane and a composite functional membrane that can simultaneously solve the problems of solvent pollution, solvent residue, MOF agglomeration and detachment, and limited substrate compatibility. Summary of the Invention
[0006] To simultaneously address the issues of solvent contamination, solvent residue, MOF agglomeration and detachment, and limited substrate compatibility, this application proposes a method for preparing a composite functional membrane and the composite functional membrane itself.
[0007] On one hand, embodiments of this application provide a method for preparing a composite functional membrane, the method comprising: S1. Provide a substrate and MOF powder; the substrate includes any one of modified nanocellulose slurry and polyolefin porous membrane; S2. The MOF powder and the aqueous powder lubricant are mixed uniformly in a dry state according to a preset mass ratio to obtain a composite powder; S3. The composite powder is uniformly sprayed onto the surface of the substrate, and the composite powder is uniformly embedded into the surface layer and micropores of the substrate by the combined physical action of mechanical rolling and micro-friction, to obtain a composite functional membrane; for the modified nanocellulose slurry, after the combined physical action of mechanical rolling and micro-friction, MOF particles are embedded into the fiber interwoven network to form a concrete-like three-dimensional network composite structure; for the polyolefin porous membrane, after the combined physical action of mechanical rolling and micro-friction, MOF particles are uniformly anchored to the membrane surface and micropore channels; S4. The composite functional film is cured at a constant temperature to enhance the interfacial bonding strength between the MOF powder and the substrate, thereby obtaining the cured functional film. S5. The cured functional film is post-processed and molded to obtain a composite functional film.
[0008] In an optional embodiment, in step S1, the modified nanocellulose slurry is anionic controlled oxidation modified nanocellulose, with a solid content controlled at 2wt%~3wt%, a fiber diameter of 100~300nm, and a surface carboxyl functional group content of 1.0mmol / g~1.5mmol / g.
[0009] In an optional embodiment, the method further includes: The substrate is pretreated to obtain a pretreated substrate; Wherein, when the substrate is modified nanocellulose slurry, the pretreatment process is: subjecting the modified nanocellulose slurry to high-pressure homogenization dispersion treatment; where the substrate is the polyolefin porous membrane, the pretreatment process is: subjecting the polyolefin membrane to dust removal and plasma activation pretreatment in sequence. Accordingly, the step of uniformly spraying the composite powder onto the surface of the substrate includes: The composite powder is uniformly sprayed onto the surface of the pretreated substrate.
[0010] In an optional embodiment, the homogenization pressure of the high-pressure homogenization and dispersion treatment is 1100 bar to 1300 bar, the number of homogenization cycles is 2 to 4, and the single fiber dispersion rate of the slurry after homogenization treatment is ≥98%. The blowing pressure during the dust removal process is 0.2MPa~0.3MPa, and the blowing distance is 10cm~15cm; The plasma activation pretreatment has an activation power of 80W~120W and an activation time of 0.5min~1.5min.
[0011] In an optional embodiment, the method further includes: The MOF powder is dried, subjected to air jet milling, and classified and sieved to obtain pretreated MOF powder; wherein the milling pressure is 0.4MPa~0.6MPa, the classification and sieving mesh is 30 mesh~80 mesh, and the pretreated MOF powder has a size of 200nm~500nm. Accordingly, the step of uniformly mixing the MOF powder with an aqueous powder lubricant in a dry state according to a preset mass ratio to obtain a composite powder includes: The pretreated MOF powder and water-based powder lubricant are mixed uniformly in a dry state according to a preset mass ratio to obtain a composite powder.
[0012] In an optional embodiment, the MOF powder includes any one or more of ZIF-8, UiO-66, and ZIF-7.
[0013] In an optional embodiment, the mass ratio of the MOF powder to the aqueous powder lubricant is 95:5 to 98:2.
[0014] In an optional embodiment, in step S3, the spray temperature is 25°C to 30°C; the spray mode is continuous uniform spray; and the spray direction is vertically upward spraying onto the substrate. The temperature of the roller pressing and friction is 25℃~35℃; the roller pressing pressure is 0.3MPa~0.8MPa; the friction method is static friction with micro-textured roller surface; the residence time of single-segment roller pressing and friction is 0.2~0.5s; the continuous rolling speed of the roll material is 4min~8m / min; and the controllable load range of MOF powder is 30~80g / ㎡.
[0015] In an optional embodiment, in step S4, the curing temperature is 25°C to 40°C, and the curing time is 10 min to 30 min. On the other hand, this application also provides a composite functional membrane, which is prepared by the preparation method described in any of the above embodiments.
[0016] Based on the above technical solution, the embodiments of this application have at least the following beneficial effects: This application provides a method for preparing a composite functional membrane, the method comprising: S1. providing a substrate and MOF powder; the substrate comprising any one of modified nanocellulose slurry and polyolefin porous membrane; S2. uniformly mixing the MOF powder with an aqueous powder lubricant in a dry state according to a preset mass ratio to obtain a composite powder; S4. uniformly spraying the composite powder onto the surface of the substrate, and using the synergistic physical action of mechanical rolling and micro-friction to drive the composite powder to uniformly embed into the surface layer and micropores of the substrate, thereby obtaining the composite functional membrane; The modified nanocellulose slurry, after mechanical rolling and micro-friction combined physical action, allows MOF particles to embed into the fiber interwoven network, forming a concrete-like three-dimensional network composite structure; for the polyolefin porous membrane, after mechanical rolling and micro-friction combined physical action, MOF particles are uniformly anchored on the membrane surface and micropore channels; S5. The composite functional membrane is cured at a constant temperature to strengthen the interfacial bonding strength between the MOF powder and the substrate, obtaining a cured functional membrane; S6. The cured functional membrane is post-processed and molded to obtain a composite functional membrane.
[0017] The present application, through the above technical solution, can achieve the following beneficial effects: 1) Addressing the dual pain points of environmental protection and safety in the industry: This application uniformly mixes the MOF powder with an aqueous powder lubricant in a dry state according to a preset mass ratio, and then sprays the composite powder evenly onto the surface of the substrate. By utilizing the combined physical action of mechanical rolling and micro-friction, the composite powder is driven to be uniformly embedded into the surface layer and micropores of the substrate. No organic solvents are involved in the entire process, completely breaking the industry's solvent-dependent technology pattern. There are zero emissions of waste and no solvent residues. This not only solves the industry problems of serious pollution and high environmental protection costs of traditional processes, but also eliminates product problems such as battery gas generation, bulging, lifespan reduction, and safety hazards caused by solvent residues, achieving a dual breakthrough in green process and high product safety.
[0018] 2) Completely solve the problem of MOF aggregation and detachment, and achieve long-term performance without degradation: When the substrate is modified nanocellulose slurry, relying on the three-dimensional concrete-like anchoring structure of modified nanocellulose, MOF particles are uniformly embedded in the fiber network nodes and gaps, forming a dual fixation effect of physical encapsulation and interfacial coordination, which effectively inhibits particle aggregation and eliminates the problem of MOF detachment and failure during long-term charge and discharge cycles, ensuring uniform performance of the diaphragm and significantly improving cycle stability; when the substrate is a polyolefin porous diaphragm, MOF particles are uniformly anchored on the diaphragm surface and micropore channels, which can also eliminate the problem of MOF detachment and failure during long-term charge and discharge cycles.
[0019] 3) Comprehensive upgrade of the core electrochemical and safety performance of the separator: MOF polar functional groups and porous structure thoroughly improve the hydrophobic defects of polyolefin separators, achieve superhydrophilic electrolyte wetting, significantly reduce battery interface impedance, and improve rate charge and discharge performance; relying on MOF sub-nanometer regular channels to achieve precise lithium ion sieving, uniformly control lithium ion deposition flux, and inhibit abnormal lithium dendrite growth from the source; high heat-resistant MOF particles and dense fiber network synergistically constrain the high-temperature deformation of the substrate, significantly reduce the high-temperature thermal shrinkage rate of the separator, and improve the high-temperature safety threshold of the battery.
[0020] 4) Dual substrate universality and strong mass production adaptability: The process of this application can be adapted to both nanofiber flexible separators and PP / PE polyolefin separator modification, covering the mainstream lithium battery separator categories; the room temperature dry continuous rolling process has simplified procedures, controllable parameters, high yield, and recyclable powder, resulting in low mass production cost and adaptability to large-scale industrial continuous production. Attached Figure Description
[0021] To more clearly illustrate the technical solutions and advantages in the embodiments of this application or related technologies, the drawings used in the description of the embodiments or related technologies will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 This is a schematic flowchart illustrating a method for preparing a composite functional membrane according to an exemplary embodiment of this application.
[0023] Figure 2 This is an exemplary embodiment of the present application, illustrating the overall flow chart of a solvent-free solid-phase preparation process for a composite functional membrane.
[0024] Figure 3 A schematic diagram of the microstructure of the MOF-modified membrane prepared by a traditional organic solvent liquid-phase process.
[0025] Figure 4 A schematic diagram of the modified nanocellulose three-dimensional network anchoring composite microstructure provided for an exemplary embodiment of this application.
[0026] Figure 5 This is a schematic diagram of the microstructure of a solvent-free solid-phase anchoring modification of a polyolefin membrane provided as an exemplary embodiment of this application. Detailed Implementation
[0027] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0028] This application provides a method for preparing a composite functional membrane. Figure 1 This is a schematic flowchart illustrating a method for preparing a composite functional membrane according to an exemplary embodiment of this application, as shown below. Figure 1 As shown, the preparation method of this composite functional membrane includes: S1. Provide a substrate and MOF powder; the substrate includes any one of modified nanocellulose slurry and polyolefin porous membrane.
[0029] Optionally, the MOF powder includes any one or more of ZIF-8, UiO-66, and ZIF-7. Using these types of powders has the following advantages: the powder has a high specific surface area and a controllable pore structure; a single MOF can endow the composite membrane with stable ion transport channels and electrolyte affinity; multiple MOFs can be combined to construct a hierarchical porous structure, combining the surface functional groups and chemical stability advantages of different MOFs to achieve synergistic performance; simultaneously, the polar sites on the MOF surface can adsorb electrolyte impurities, suppress interfacial side reactions, and improve the ion conductivity and electrochemical stability of the composite functional membrane.
[0030] Optionally, the modified nanocellulose slurry (using the modified nanocellulose in patent application number 201811534380.1) is anionic controlled oxidation modified nanocellulose, with a solid content controlled at 2wt%~3wt%, a fiber diameter of 100~300nm, and a surface carboxyl functional group content of 1.0mmol / g~1.5mmol / g. It has excellent interweaving molding properties and interfacial anchoring activity, and can stably encapsulate and fix MOF particles to construct a high-strength composite network architecture.
[0031] S2. The MOF powder and the water-based powder lubricant are mixed uniformly in a dry state according to a preset mass ratio to obtain a composite powder.
[0032] Optionally, the water-based powder lubricant is a CMC water-based lubricating powder additive (sodium carboxymethyl cellulose water-based lubricating powder additive). MOF powder and CMC water-based lubricating powder additive can be uniformly mixed at room temperature in a mass ratio of 95:5 to 98:2, without solvents or liquid phases throughout the process, to obtain a uniformly dispersed composite functional powder.
[0033] In an optional embodiment, prior to S2, the above method may further include: The MOF powder is dried, subjected to air jet milling, and graded sieving to control the powder particle size to 200-500 nm, removing large agglomerated particles to obtain monodisperse dried MOF powder for later use, thus obtaining pretreated MOF powder. The air jet milling uses high-purity dry nitrogen as the gas source, with a milling pressure of 0.4 MPa-0.6 MPa. The grading sieve mesh size is 30-80 mesh. The pretreated MOF powder has a particle size of 200-500 nm, and the coefficient of variation of powder dispersion uniformity is ≤5%. A pre-treatment low-temperature drying process at 60℃ for 2 hours is performed to thoroughly remove adsorbed moisture from the powder.
[0034] The embodiments of this application set the above parameters in the pretreatment stage of MOF, which can achieve the following beneficial effects: ① Nitrogen gas flow pulverization has no powder contamination and no oxidation damage, preserving the complete pore structure and ion sieving performance of MOF; ② The particle size range of 200~500nm can perfectly match the micropores and fiber gaps of the substrate, avoiding both the inability of large particles to embed and the resulting surface accumulation and detachment, and the inability of ultrafine particles to penetrate the substrate and cause load loss; ③ Graded sieving ensures the monodispersity of powder, eliminating MOF agglomeration from the source, and laying the foundation for uniform anchoring and long-term stable modification.
[0035] Accordingly, step S2 may include: mixing the pretreated MOF powder with an aqueous powder lubricant in a dry state according to a preset mass ratio to obtain a composite powder.
[0036] S3. The composite powder is uniformly sprayed onto the surface of the substrate, and the composite powder is uniformly embedded into the surface layer and micropores of the substrate by the combined physical action of mechanical rolling and micro-friction, to obtain a composite functional membrane; for the modified nanocellulose slurry, after the combined physical action of mechanical rolling and micro-friction, MOF particles are embedded into the fiber interwoven network to form a concrete-like three-dimensional network composite structure; for the polyolefin porous membrane, after the combined physical action of mechanical rolling and micro-friction, MOF particles are uniformly anchored to the membrane surface and micropore channels.
[0037] Optionally, in step S3, the substrate can be placed in a continuous solid-phase composite equipment, and the composite powder can be uniformly sprayed onto the surface of the substrate using a weightless precision feeding system. The MOF powder is driven to uniformly embed into the surface layer and micropores of the substrate by the combined physical action of mechanical roller pressing and micro-friction. The spraying temperature is 25℃~30℃ (no heating or low-temperature cooling throughout the process); the spraying mode is continuous and uniform spraying, without interruption or repeated spraying; the spraying direction is vertically upward towards the substrate (directly facing the upper surface of the roll); the feeding accuracy is ±0.5g / ㎡; the spraying rate is synchronized with the roll speed of 4~8m / min; the spraying is completed in a single pass without secondary spraying. The advantages of setting these parameters are as follows: ① Room temperature spraying has no temperature stress, which will not cause thermal deactivation of MOF powder or deformation of the substrate, thus preserving the original performance of the material; ② Vertical unidirectional continuous spraying can ensure uniform coverage of the powder throughout the entire area, with no local accumulation or blank areas, and extremely high load consistency; ③ Linked precision feeding can match different walking speeds and different loads (30~80g / ㎡) to meet customized needs, and is suitable for continuous mass production; ④ The single-pass spraying process is simplified, improving production efficiency and reducing mass production capacity consumption and costs.
[0038] Optionally, the temperature of the rolling and friction is 25℃~35℃ (dry state at room temperature throughout, without heating or cooling); the rolling pressure is 0.3MPa~0.8MPa; the friction method is static friction with micro-textured roller surface, without dynamic high-speed friction; the residence time of single-segment rolling friction is 0.2~0.5s; the continuous rolling speed of the roll material is 4min~8m / min; the rolling roller is a silicone elastic roller with a hardness of 60~70HA; and the controllable load range of MOF powder is 30~80g / ㎡. The advantages of setting these parameters are as follows: ① Room temperature roller pressing friction completely avoids damage to MOF channels and substrate structure caused by high temperature, with no thermal deformation and no performance degradation; ② The synergistic effect of elastic roller pressing and micro-friction can gently drive MOF powder to embed into the substrate surface and micropores, achieving physical anchoring without puncturing or scratching the substrate; ③ Short-time rapid roller pressing adapts to continuous production lines, with efficient processes, while ensuring uniform powder embedding depth and preventing powder loss and detachment in the later stages; ④ Wide and stable parameter range, high tolerance for mass production errors, and good batch consistency.
[0039] In an optional embodiment, prior to step S3, the method may further include: The substrate is pretreated to obtain a pretreated substrate; In the case where the substrate is a modified nanocellulose slurry, the pretreatment process is as follows: the modified nanocellulose slurry is subjected to high-pressure homogenization dispersion treatment; in the case where the substrate is the polyolefin porous membrane, the pretreatment process is as follows: the polyolefin membrane is subjected to dust removal and plasma activation pretreatment in sequence to remove surface oil, dust and inert surface layer, and improve the anchoring and adsorption capacity of the substrate.
[0040] Optionally, the homogenizing equipment for the high-pressure homogenization and dispersion treatment adopts a high-pressure micro-jet homogenizer, with a homogenization pressure of 1100 bar to 1300 bar, a homogenization cycle of 2 to 4 times, and a single fiber dispersion rate of ≥98% after homogenization, with no fiber agglomerates, no large particle impurities, and a slurry uniformity deviation of ≤2%. The advantages of setting these parameters are as follows: ① The high-pressure shear force of 1100~1300 bar can completely disperse the modified nanocellulose agglomerates, achieving single fiber dispersion and ensuring the dense and uniform three-dimensional interwoven network in the subsequent process; ② The 2 to 4 cycles of homogenization can accurately retain the fiber target diameter of 100~300 nm, avoiding fiber breakage and decreased mechanical strength due to excessive homogenization; ③ Stable homogenization parameters can ensure the consistency of batch slurries, providing a regular skeletal foundation for the uniform embedding and encapsulation of MOF particles, and eliminating local structural defects in the subsequent composite membrane.
[0041] Optionally, the dust removal process takes place in a Class 10,000 cleanroom, using high-pressure clean nitrogen purging at a pressure of 0.2MPa~0.3MPa and a distance of 10cm~15cm, with bidirectional forward and reverse purging. After dust removal, the residual dust and impurities on the substrate surface are ≤0.1mg / ㎡. Optionally, the plasma activation pretreatment uses low-temperature air plasma activation at a power of 80W~120W, an activation time of 0.5min~1.5min, and an activation distance of 8~12mm. The entire process is performed at low temperature and ambient temperature, preventing high-temperature damage to the substrate. The advantages of setting these parameters are as follows: ① Dust-free cleaning can thoroughly remove oil and dust from the surface of polyolefin separators, preventing impurities from hindering the bonding between MOF and substrate, and preventing localized powder shedding and uneven wetting in the later stages; ② Low-temperature shallow activation can precisely break the inert hydrophobic surface layer of PP / PE separators, improving the surface energy and anchoring adsorption capacity of the substrate, while not damaging the mechanical structure and micropore morphology of the separator itself; ③ The shallow activation mode avoids excessive etching, ensuring the integrity of the substrate and adapting to continuous mass production.
[0042] Accordingly, in step S3 above, the uniform spraying of the composite powder onto the surface of the substrate includes: The composite powder is uniformly sprayed onto the surface of the pretreated substrate.
[0043] It should be noted that the solvent-free solid-phase one-step composite technology described in step S3 is a pure physical-mechanical composite mechanism. It requires no solvent, no high-temperature sintering, no substrate damage, and no solvent residue. It completely breaks the industry's technical prejudice that traditional MOF modification relies on organic solvents and can be adapted to one-stop green functional modification of nanofiber substrates and PP / PE polyolefin substrates.
[0044] S4. The composite functional film is cured at a constant temperature to enhance the interfacial bonding strength between the MOF powder and the substrate, thereby obtaining the cured functional film.
[0045] Optionally, the composite functional film can be placed in a dust-free constant temperature environment of 25℃~40℃ and allowed to stand for curing for 10min~30min to strengthen the interfacial bonding strength between MOF powder and substrate and prevent powder shedding and peeling.
[0046] S5. The cured functional film is post-processed and molded to obtain a composite functional film.
[0047] Optionally, the cured functional membrane can be flattened, rolled up, precisely slit, subjected to full-area dust removal and performance testing, and qualified products can be screened to obtain nanofiber MOF composite functional membrane and polyolefin-based MOF composite lithium battery separator respectively.
[0048] The present application, through the above technical solution, can achieve the following beneficial effects: 1) Addressing the dual pain points of environmental protection and safety in the industry: This application uniformly mixes the MOF powder with an aqueous powder lubricant in a dry state according to a preset mass ratio, and then sprays the composite powder evenly onto the surface of the substrate. By utilizing the combined physical action of mechanical rolling and micro-friction, the composite powder is driven to be uniformly embedded into the surface layer and micropores of the substrate. No organic solvents are involved in the entire process, completely breaking the industry's solvent-dependent technology pattern. There are zero emissions of waste and no solvent residues. This not only solves the industry problems of serious pollution and high environmental protection costs of traditional processes, but also eliminates product problems such as battery gas generation, bulging, lifespan reduction, and safety hazards caused by solvent residues, achieving a dual breakthrough in green process and high product safety.
[0049] Figure 2 This is an exemplary embodiment of the present application, illustrating the overall flow chart of a solvent-free solid-phase preparation process for a composite functional membrane. Figure 2 This flowchart fully demonstrates the completely dry preparation process of this application, which differs from traditional liquid-phase processes. It mainly includes substrate classification and pretreatment, dry pretreatment of MOF powder, solvent-free dry mixing of powder, room-temperature solid-phase precision spraying and rolling lamination, low-temperature isothermal anchoring and curing, and finished product winding, slitting, and inspection. This application does not introduce any organic solvents throughout the entire process, has no liquid-phase treatment steps, and features a streamlined and continuous process with no substrate damage and no waste generation. The flowchart visually illustrates the pioneering room-temperature solvent-free one-step solid-phase lamination process of this application, breaking through the industry's technical bias that traditional MOF modification relies on organic solvents, and providing process support for green, continuous, and large-scale mass production.
[0050] 2) Completely solve the problem of MOF aggregation and detachment, and achieve long-term performance without degradation: When the substrate is modified nanocellulose slurry, relying on the three-dimensional concrete-like anchoring structure of modified nanocellulose, MOF particles are uniformly embedded in the fiber network nodes and gaps, forming a dual fixation effect of physical encapsulation and interfacial coordination, which effectively inhibits particle aggregation and eliminates the problem of MOF detachment and failure during long-term charge and discharge cycles, ensuring uniform performance of the diaphragm and significantly improving cycle stability; when the substrate is a polyolefin porous diaphragm, MOF particles are uniformly anchored on the diaphragm surface and micropore channels, which can also eliminate the problem of MOF detachment and failure during long-term charge and discharge cycles.
[0051] Figure 3 A schematic diagram of the microstructure of the MOF-modified membrane prepared by a traditional organic solvent liquid-phase process. Figure 3 It is known that MOF nanoparticles in traditional liquid-phase processes suffer from severe agglomeration and uneven particle size distribution. Furthermore, the MOF particles are loosely attached to the membrane substrate surface only through physical adsorption, without embedding themselves into the microporous structure within the substrate. This results in significant gaps and delamination defects at the particle-substrate interface. These structural characteristics directly lead to defects in traditional modified membranes, such as easy MOF detachment, poor structural stability, severe solvent residue, and reduced battery cycle life. This clearly demonstrates the inherent flaws of the existing technology and provides strong evidence for the necessity of the technical improvements proposed in this application.
[0052] Figure 4 A schematic diagram of the modified nanocellulose three-dimensional network anchoring composite microstructure provided for an exemplary embodiment of this application. Figure 4 This application clearly demonstrates its unique dual-stabilizing structure of "network embedding + interface coordination anchoring": modified nanocellulose constructs a dense three-dimensional interwoven network, with MOF particles completely embedded within the gaps and cavities of the fiber network, achieving all-round physical encapsulation and constraint; simultaneously, relying on the highly active carboxyl groups on the fiber surface to form interface coordination bonds with MOF metal sites, a stable composite architecture similar to concrete is constructed. This structure fundamentally solves the industry problems of MOF particle agglomeration, uneven dispersion, and cyclic shedding, significantly improving the structural integrity and electrochemical cycling stability of the composite membrane, directly reflecting the core structural innovation of this application.
[0053] Specifically, "network-embedded packages" are manifested as follows: Figure 4 The continuously interwoven modified nanocellulose fiber skeleton forms a three-dimensional network of pores and interwoven nodes. MOF particles (spherical high-brightness particles) are completely embedded in the internal gaps and interwoven node cavities of the fiber network, and do not remain on the fiber surface. They are surrounded, wrapped, and constrained by multiple layers of nanofibers, with no exposed or suspended particles. This directly reflects the "network embedded and wrapped" characteristic, which can physically restrict the aggregation and displacement of MOF particles.
[0054] "Interface alignment and anchoring" is specifically manifested as follows: Figure 4 There are no obvious gaps or delamination at the interface between the MOF particles and the modified nanocellulose fibers. Relying on the high-density active carboxyl groups (-COOH) on the fiber surface, they form stable coordination bonds with the metal active sites of MOF. The interface is tightly and firmly bonded, which is different from the adhesion state of traditional physical adsorption. It directly reflects the "interfacial coordination anchoring" feature and prevents particle detachment and failure from the chemical interface level.
[0055] Figure 5 This is a schematic diagram of the microstructure of a solvent-free solid-phase anchoring modification of a polyolefin membrane provided as an exemplary embodiment of this application. Figure 5 This study demonstrates how a PP / PE polyolefin substrate, after dust-free cleaning and shallow plasma activation, can be composited at room temperature using dry roller pressing. This process uniformly anchors monodisperse MOF powder within the micropores and surface channels of a membrane surface, resulting in uniform particle distribution without agglomeration or accumulation. The particles tightly interlock with the micropore walls of the substrate, forming a stable physical anchoring structure. This structure proves that the solid-phase process described in this application is effectively adaptable to commercially available rigid polyolefin substrates, requiring no solvents and causing no substrate etching damage. It simultaneously achieves hydrophilic modification of the membrane, ion sieving, and suppression of high-temperature thermal shrinkage, overcoming the technical barrier of traditional processes that only adapt to a single substrate.
[0056] 3) Comprehensive upgrade of the core electrochemical and safety performance of the separator: MOF polar functional groups and porous structure thoroughly improve the hydrophobic defects of polyolefin separators, achieve superhydrophilic electrolyte wetting, significantly reduce battery interface impedance, and improve rate charge and discharge performance; relying on MOF sub-nanometer regular channels to achieve precise lithium ion sieving, uniformly control lithium ion deposition flux, and inhibit abnormal lithium dendrite growth from the source; high heat-resistant MOF particles and dense fiber network synergistically constrain the high-temperature deformation of the substrate, significantly reduce the high-temperature thermal shrinkage rate of the separator, and improve the high-temperature safety threshold of the battery.
[0057] Experimental verification showed that commercially available pure PP separators exhibited the fastest capacity decay, with no data available after 450 cycles, the curve discontinuing, and the shortest cycle life. Traditional liquid-phase modified separators also showed no data available after 720 cycles, the curve discontinuing, exhibiting mid-term capacity fluctuations and rapid decay in the later stages, corresponding to solvent residue and MOF detachment defects. The nanofiber MOF composite separator of this application showed the highest capacity retention rate and the slowest decay throughout the cycle. The modified PP composite separator of this application had performance second only to the nanofiber system. It is evident that the two types of composite separators in this application exhibited smooth capacity decay without abrupt performance changes, and their cycle life was significantly superior to existing technologies. This spectral analysis quantitatively demonstrates that the solvent-free solid-phase anchoring process of this application can significantly improve battery cycle stability and service life, possessing unexpectedly excellent technical effects.
[0058] 4) Dual substrate universality and strong mass production adaptability: The process of this application can be adapted to both nanofiber flexible separators and PP / PE polyolefin separator modification, covering the mainstream lithium battery separator categories; the room temperature dry continuous rolling process has simplified procedures, controllable parameters, high yield, and recyclable powder, resulting in low mass production cost and adaptability to large-scale industrial continuous production.
[0059] This application also provides a composite functional membrane, which is prepared by the preparation method described in any of the above embodiments.
[0060] This application also provides an application of a composite functional membrane in the fields of lithium-ion batteries and aqueous energy storage battery separators. It has the characteristics of superhydrophilicity, low interfacial impedance, long-lasting lithium dendrite suppression, high-temperature thermal stability, no solvent residue, and green and pollution-free properties.
[0061] This application also provides a series of embodiments to further verify the implementation effect of the glass fiber electronic cloth and its preparation method in this application. The implementation effect of the technical solution of this application will be described in detail below with reference to specific embodiments.
[0062] Example 1 (Substrate is modified nanocellulose slurry): S1. Substrate pretreatment: Modified nanocellulose slurry with a solid content of 2.5wt% is used. It is homogenized three times by high pressure micro-jet at 1200bar to obtain a uniformly dispersed nanocellulose slurry with uniform particle size. It is then coated and molded into a wet nanofiber membrane for later use. S2, MOF powder pretreatment: ZIF-8 powder was selected, dried at 60℃ for 2 hours, and then obtained as a monodisperse uniform powder with a particle size of 300nm by air jet milling and sieving. S3. Dry mixing: Mix ZIF-8 powder and CMC additive at a mass ratio of 97:3, stir dry at room temperature for 15 minutes, and mix evenly to obtain composite powder; S4. Solid-phase composite: The wet nanofiber membrane roll travels at a speed of 6m / min, with a roller pressure of 0.5MPa. The composite powder is precisely sprayed to allow MOF particles to be deeply embedded in the nanofiber interwoven network, forming a concrete-like three-dimensional stable composite structure. S5. Curing and shaping: Curing in a constant temperature and dust-free environment at 30℃ for 20 minutes to enhance the interfacial bonding force; S6. Post-processing: After flattening, winding, precision cutting, and performance testing, a nanofiber MOF composite functional membrane is obtained.
[0063] Experiments have verified that the electrolyte in this embodiment has a wetting angle of 22°; a thermal shrinkage rate of 5.1% at 120℃ / 30min; a battery cycle life of 1250 cycles; no MOF shedding after 1200 cycles; and the preparation process involves zero organic solvents, zero waste, and no solvent residue, making it green and suitable for mass production.
[0064] Example 1-1 (Substrate is modified nanocellulose slurry): The modified nanocellulose slurry has a solid content of 2wt%, is homogenized under high pressure of 1100 bar, and is homogenized twice; the MOF powder has a particle size of 200 nm; the MOF:CMC ratio is 98:2, and it is dry-stirred for 10 min; the roll speed is 4 m / min, the roller pressure is 0.3 MPa; the curing temperature is 25℃, and the curing time is 10 min.
[0065] The remaining process is the same as in Example 1.
[0066] Experiments have verified that the electrolyte in this embodiment has a wetting angle of 25°; a thermal shrinkage rate of 6.2% at 120℃ / 30min; a battery cycle life of 1120 cycles; no MOF shedding after 1200 cycles; and the preparation process involves zero organic solvents, zero waste, and no solvent residue, making it green and suitable for mass production.
[0067] Examples 1-2 (substrate is modified nanocellulose slurry): The modified nanocellulose slurry has a solid content of 3wt%, is homogenized under high pressure of 1300 bar for 4 times, has a MOF powder particle size of 500 nm, a MOF:CMC ratio of 95:5, is dry-stirred for 20 min, has a roll speed of 8 m / min, a roller pressure of 0.8 MPa, and a curing temperature of 40℃ for 30 min.
[0068] The remaining process is the same as in Example 1.
[0069] Experiments have verified that the electrolyte in this embodiment has a wetting angle of 20°; a thermal shrinkage rate of 4.7% at 120℃ / 30min; a battery cycle life of 1300 cycles; no MOF shedding after 1200 cycles; and the preparation process involves zero organic solvents, zero waste, and no solvent residue, making it green and suitable for mass production.
[0070] Example 2 (substrate is PP polyolefin substrate): S1. Substrate pretreatment: Commercial lithium battery PP separator is selected and subjected to dust removal and plasma activation treatment for 1 minute to remove surface impurities and inert surface layer, thereby improving the adsorption and anchoring performance of the substrate. S2, MOF powder pretreatment: Same as in Example 1, prepare 300nm monodisperse ZIF-8 uniform powder; S3, Dry mixing: Prepare composite powder using the same proportions as in Example 1; S4. Solid-phase composite: The PP diaphragm roll travels at a speed of 5m / min and the rolling pressure is 0.4MPa. Through a solvent-free solid-phase one-step composite process, MOF particles are uniformly anchored to the micropores and surface of the PP diaphragm. S5. Curing and shaping: Curing at a constant temperature of 28℃ for 15 minutes to stabilize the interface bonding state; S6. Post-processing: After performance testing, winding and slitting, a modified PP-based MOF composite lithium battery separator is obtained.
[0071] Experiments have verified that the electrolyte in this embodiment has a wetting angle of 24°; a thermal shrinkage rate of 7.4% at 120℃ / 30min; a battery cycle life of 1180 cycles; no MOF shedding after 1200 cycles; and the preparation process involves zero organic solvents, zero waste, and no solvent residue, making it green and suitable for mass production.
[0072] Example 2-1: (Lower limit parameter) Process parameter settings: PP diaphragm plasma activation power 80W, activation 0.5min; MOF powder particle size 200nm; MOF:CMC=98:2, dry stirring 10min; roll speed 8m / min, roller pressure 0.3MPa; curing temperature 25℃, curing 10min.
[0073] Experiments have verified that the electrolyte in this embodiment has a wetting angle of 27°; a thermal shrinkage rate of 8.8% at 120℃ / 30min; a battery cycle life of 1050 cycles; no MOF shedding after 1200 cycles; and the preparation process involves zero organic solvents, zero waste, and no solvent residue, making it green and suitable for mass production.
[0074] Example 2-2: (Upper Limit Parameter) Process parameter settings: PP diaphragm plasma activation power 120W, activation 1.5min; MOF powder particle size 500nm; MOF:CMC=95:5, dry stirring 20min; roll speed 4m / min, roller pressure 0.8MPa; curing temperature 40℃, curing 30min.
[0075] Experiments have verified that the electrolyte in this embodiment has a wetting angle of 22°; a thermal shrinkage rate of 6.5% at 120℃ / 30min; a battery cycle life of 1220 cycles; no MOF shedding after 1200 cycles; and the preparation process involves zero organic solvents, zero waste, and no solvent residue, making it green and suitable for mass production.
[0076] Comparative Example 1 (Ordinary unmodified nanocellulose): The substrate was replaced with ordinary unmodified nanocellulose, which has no highly active carboxyl anchoring sites. The remaining process parameters, powder ratio, loading, and testing environment were completely consistent with those in Example 1.
[0077] Experiments have verified that the electrolyte in this embodiment has a wetting angle of 35°; a thermal shrinkage rate of 12.3% at 120℃ / 30min; a battery cycle life of 680 cycles; and significant MOF shedding after 400 cycles. The preparation process is free of solvent contamination, but the modification performance is poor and the structure is unstable.
[0078] Therefore, it can be seen that the highly active carboxyl-modified nanocellulose defined in the embodiments of this application can construct a three-dimensional anchoring network. Compared with ordinary nanocellulose, it can significantly improve the wettability, high-temperature dimensional stability and cycle life of the membrane, and solve the problem of MOF detachment failure from the root, proving that the substrate selection of this application has unique advantages and inventiveness.
[0079] Comparative Example 2: Commercial PP membranes were used, and the traditional DMF solvent wet coating process was replaced. The MOF loading, substrate specifications, and testing environment were completely consistent with those in Example 2.
[0080] Experiments have verified that the electrolyte in this embodiment has a wetting angle of 26°; a thermal shrinkage rate of 8.9% at 120℃ / 30min; a battery cycle life of 850 cycles; significant MOF detachment after 600 cycles; and the preparation process generates DMF organic waste liquid and VOC waste gas, posing a serious risk of solvent residue.
[0081] The performance data of the above embodiments can be found in Table 1. As can be seen from Table 1, compared with the industry-standard traditional liquid phase process, the solvent-free room temperature solid phase composite process of this application can simultaneously achieve performance upgrade and green production, and completely solve industry defects such as solvent pollution, solvent residue, easy MOF detachment, and battery cycle degradation.
[0082] Table 1
[0083] It should be noted that the order of the embodiments described above is merely for descriptive purposes and does not represent the superiority or inferiority of the embodiments. Furthermore, specific embodiments have been described above. Other embodiments are within the scope of the appended claims. In some cases, the actions or steps described in the claims can be performed in a different order than that shown in the embodiments and still achieve the desired result. Additionally, the processes depicted in the drawings do not necessarily require a specific or sequential order to achieve the desired result. In some embodiments, multitasking and parallel processing are also possible or may be advantageous.
[0084] The various embodiments in this specification are described in a progressive manner. The same or similar parts between the various embodiments can be referred to each other. Each embodiment focuses on describing the differences from other embodiments.
[0085] It should be noted that all features described in the embodiments of this application (including technical features described in different embodiments) can be combined arbitrarily under reasonable circumstances, and the new technical solutions formed by the combination are all within the protection scope of the embodiments of this application. The above description is only some embodiments of the embodiments of this application and is not intended to limit the embodiments of this application. Those skilled in the art should understand that there will be various changes and improvements to the embodiments of this application, and any modifications, equivalent substitutions and improvements made in accordance with the embodiments of this application fall within the protection scope claimed by the embodiments of this application.
Claims
1. A method for preparing a composite functional membrane, characterized in that, The preparation method includes: S1. Provide a substrate and MOF powder; the substrate includes any one of modified nanocellulose slurry and polyolefin porous membrane; S2. The MOF powder and the aqueous powder lubricant are mixed uniformly in a dry state according to a preset mass ratio to obtain a composite powder; S3. The composite powder is uniformly sprayed onto the surface of the substrate, and the composite powder is uniformly embedded into the surface layer and micropores of the substrate by the combined physical action of mechanical rolling and micro-friction, to obtain a composite functional membrane; for the modified nanocellulose slurry, after the combined physical action of mechanical rolling and micro-friction, MOF particles are embedded into the fiber interwoven network to form a concrete-like three-dimensional network composite structure; for the polyolefin porous membrane, after the combined physical action of mechanical rolling and micro-friction, MOF particles are uniformly anchored to the membrane surface and micropore channels; S4. The composite functional film is cured at a constant temperature to enhance the interfacial bonding strength between the MOF powder and the substrate, thereby obtaining the cured functional film. S5. The cured functional film is post-processed and molded to obtain a composite functional film.
2. The preparation method according to claim 1, characterized in that, In step S1, the modified nanocellulose slurry is anionic controlled oxidation modified nanocellulose, with a solid content controlled at 2wt%~3wt%, a fiber diameter of 100~300nm, and a surface carboxyl functional group content of 1.0mmol / g~1.5mmol / g.
3. The method according to claim 1, characterized in that, The method further includes: The substrate is pretreated to obtain a pretreated substrate; Wherein, when the substrate is modified nanocellulose slurry, the pretreatment process is: subjecting the modified nanocellulose slurry to high-pressure homogenization dispersion treatment; where the substrate is the polyolefin porous membrane, the pretreatment process is: subjecting the polyolefin membrane to dust removal and plasma activation pretreatment in sequence. Accordingly, the step of uniformly spraying the composite powder onto the surface of the substrate includes: The composite powder is uniformly sprayed onto the surface of the pretreated substrate.
4. The method according to claim 3, characterized in that, The high-pressure homogenization and dispersion treatment involves a homogenization pressure of 1100 bar to 1300 bar, a homogenization cycle of 2 to 4 times, and a single fiber dispersion rate of ≥98% in the slurry after homogenization. The blowing pressure during the dust removal process is 0.2MPa~0.3MPa, and the blowing distance is 10cm~15cm; The plasma activation pretreatment has an activation power of 80W~120W and an activation time of 0.5min~1.5min.
5. The method according to claim 1, characterized in that, The method further includes: The MOF powder is dried, subjected to air jet milling, and classified and sieved to obtain pretreated MOF powder; wherein the milling pressure is 0.4MPa~0.6MPa, the classification and sieving mesh is 30 mesh~80 mesh, and the pretreated MOF powder has a size of 200nm~500nm. Accordingly, the step of uniformly mixing the MOF powder with an aqueous powder lubricant in a dry state according to a preset mass ratio to obtain a composite powder includes: The pretreated MOF powder and water-based powder lubricant are mixed uniformly in a dry state according to a preset mass ratio to obtain a composite powder.
6. The method according to claim 1, characterized in that, The MOF powder includes any one or more of ZIF-8, UiO-66, and ZIF-7.
7. The method according to claim 1, characterized in that, The mass ratio of the MOF powder to the aqueous powder lubricant is 95:5 to 98:
2.
8. The method according to claim 1, characterized in that, In step S3, the spray temperature is 25℃~30℃; the spray mode is continuous uniform spray; and the spray direction is vertical upward spraying onto the substrate. The temperature of the roller pressing and friction is 25℃~35℃; the roller pressing pressure is 0.3MPa~0.8MPa; the friction method is static friction with micro-textured roller surface. The single-segment roller friction residence time is 0.2~0.5s; the continuous rolling speed of the roll material is 4min~8m / min; and the controllable load range of MOF powder is 30~80g / ㎡.
9. The method according to claim 1, characterized in that, In step S4, the curing temperature is 25℃~40℃, and the curing time is 10min~30min.
10. A composite functional membrane, characterized in that, The composite functional membrane is prepared by any one of the preparation methods described in claims 1 to 9.
Citation Information
Patent Citations
Coated diaphragm and preparation method thereof
CN111326697A